2020
DOI: 10.1073/pnas.2009852117
|View full text |Cite
|
Sign up to set email alerts
|

Polyamorphism of vapor-deposited amorphous selenium in response to light

Abstract: Enhanced surface mobility is critical in producing stable glasses during physical vapor deposition. In amorphous selenium (a-Se) both the structure and dynamics of the surface can be altered when exposed to above-bandgap light. Here we investigate the effect of light on the properties of vapor-deposited a-Se glasses at a range of substrate temperatures and deposition rates. We demonstrate that deposition both under white light illumination and in the dark results in thermally and kinetically stable glasses. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…The presence of magnetic fields during deposition may also play a role in molecules containing magnetic atoms. Or illumination of the substrate during growth may affect the formation of semiconductor molecules with homo-lumo levels lower than the energy of the incident light [41]. Another property that is very useful in understanding some of the unusual properties of stable organic glasses is density.…”
Section: Organic Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of magnetic fields during deposition may also play a role in molecules containing magnetic atoms. Or illumination of the substrate during growth may affect the formation of semiconductor molecules with homo-lumo levels lower than the energy of the incident light [41]. Another property that is very useful in understanding some of the unusual properties of stable organic glasses is density.…”
Section: Organic Glassesmentioning
confidence: 99%
“…Amorphous selenium has also been grown as a thin film from the vapor in the range of temperatures and growth rates that could lead to high stability [41]. In addition, since a-Se is very sensitive to above-band gap visible light, white illumination was used during growth to investigate the effect of this parameter.…”
Section: Chalcogenide Glassesmentioning
confidence: 99%
“…For example, at high pressures, high-and low-density supercooled water phases are interconvertible through a first-order phase transition (27,28). Recent studies have demonstrated that such polyamorphic states can also be accessed through PVD in hydrogen-bonding systems with polymorphic crystal states at depositions above the nominal Tg (29,30). However, these structure-specific transitions do not provide a general resolution for the Kauzmann crisis.…”
Section: Significancementioning
confidence: 99%
“…In this way, photon activation indeed fluidizes a glass at temperatures substantially below the usual glass transition. These rearrangements may be able to allow access locally to still deeper parts of the energy landscape, ,, perhaps providing a new route to ultrastability. In any event, such photon-activated transformations also allow glasses to encode and store information.…”
Section: Theory Of Glass Dynamicsmentioning
confidence: 99%